2004
DOI: 10.1590/s0102-09352004000500007
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da infusão contínua de cetamina sobre a pressão intra-ocular em cães hipovolêmicos anestesiados com desflurano

Abstract: RESUMOCompararam-se os efeitos de duas doses de cetamina, administradas em infusão contínua, sobre a pressão intra-ocular (PIO) de 18 cães submetidos à hipovolemia e à anestesia com desflurano. Promoveu-se a hipovolemia em todos os cães, retirando-se 40 ml de sangue/kg de peso. A anestesia foi induzida com desflurano, através de máscara facial, até que a intubação orotraqueal fosse permitida. Decorridos 30 minutos, para estabilização dos parâmetros, iniciou-se a infusão contínua de cetamina. Os cães foram dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Dogs maintained in left-side position did not present alterations in IOP levels in either eye (Honsho et al 2004), however another study demonstrated a 2-3 mmHg difference in the IOP value depending on the decubitus studied (dorsal, ventral, seated) (Broadwater et al 2010). Furthermore, the authors relate the importance of maintaining the animals in the same position prior to measuring IOP and always using the same position to annul the effects that body position may have on the obtained results (Broadwater et al 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Dogs maintained in left-side position did not present alterations in IOP levels in either eye (Honsho et al 2004), however another study demonstrated a 2-3 mmHg difference in the IOP value depending on the decubitus studied (dorsal, ventral, seated) (Broadwater et al 2010). Furthermore, the authors relate the importance of maintaining the animals in the same position prior to measuring IOP and always using the same position to annul the effects that body position may have on the obtained results (Broadwater et al 2008).…”
Section: Discussionmentioning
confidence: 96%